MENINJAU IMPLEMENTASI KEBIJAKAN PENDIDIKAN INKLUSIF - Yayan Mulyana; Dedi Restendi (Balai Diklat Keagamaan Bandung, 2022)
Inclusive education for persons with disabilities has a direct impact on human resources readiness. They are ready to work and employed by the professional world. The purpose of this study is to obtain an overview of inclusive education regulation and its application. The method used in collecting data is by using secondary data method. Literature studies are obtained from supporting journals or articles. The results showed that there are already regulations governing inclusive education implementation. At the level of implementing, there are a lot of works to be done.